Low-temperature solid-phase synthesis of graphene thin films usable in the harsh environment of liquids - Giri, Suresh; Gupta, Vikaskumar Pradeepkumar; Ngatiman, Muzzammil; Abd Rahim, Nur Sahiera; Yoshida, Naoko; Yan, Jiaxin; Chua, Daniel H.C.; Lin, Wei Ming; Asaka, Toru; Yaakob, Yazid; Miyazaki, Hidetoshi; Kurushima, Kosuke; et al. (John Wiley and Sons Inc, 2025)
The synthesis of graphene at lower temperatures remains challenging, along with the expansion of its application areas. Here we demonstrated the graphene synthesis on various substrates at and above 350°C by a solid phase reaction method. In this method, C-rich Ni–C films are deposited on the substrates by conventional magnetron sputter deposition at room temperature with a binary target, followed by vacuum annealing. This resulted in phase separation of the multilayer graphene on top. The temperature dependence of graphene formation is investigated by high-resolution transmission electron microscopy (TEM), in situ X-ray diffraction (XRD) and Raman spectroscopy. Graphene thus synthesized on a stainless steel (SS) plate is successfully used to enhance the biofilm formation and the current generation by Geobacter species for use in microbial fuel cell application. As transfer-free graphene can be synthesized directly on substrates irrespective of their material and shape, and is usable in harsh environment of liquid, this simple method is believed to be quite promising for a variety of applications.